Triosephosphate Isomerase Is Dispensable In Vitro yet Essential for Mycobacterium tuberculosis To Establish Infection - Carolina Trujillo (American Society for Microbiology, 2014)
ABSTRACT Triosephosphate isomerase (TPI) catalyzes the interconversion of dihydroxyacetone phosphate (DHAP) and glyceraldehyde-3-phosphate (G3P). This reaction is required for glycolysis and gluconeogenesis, and tpi has been predicted to be essential for growth of Mycobacterium tuberculosis. However, when studying a conditionally regulated tpi knockdown mutant, we noticed that depletion of TPI reduced growth of M. tuberculosis in media containing a single carbon source but not in media that contained both a glycolytic and a gluconeogenic carbon source. We used such two-carbon-source media to isolate a tpi deletion (Δtpi) mutant. The Δtpi mutant did not survive with single carbon substrates but grew like wild-type (WT) M. tuberculosis in the presence of both a glycolytic and a gluconeogenic carbon source. 13C metabolite tracing revealed the accumulation of TPI substrates in Δtpi and the absence of alternative triosephosphate isomerases and metabolic bypass reactions, which confirmed the requirement of TPI for glycolysis and gluconeogenesis in M. tuberculosis. The Δtpi strain was furthermore severely attenuated in the mouse model of tuberculosis, suggesting that M. tuberculosis cannot simultaneously access sufficient quantities of glycolytic and gluconeogenic carbon substrates to establish infection in mice. IMPORTANCE The importance of central carbon metabolism for the pathogenesis of M. tuberculosis has recently been recognized, but the consequences of depleting specific metabolic enzymes remain to be identified for many enzymes. We investigated triosephosphate isomerase (TPI) because it is central to both glycolysis and gluconeogenesis and had been predicted to be essential for growth of M. tuberculosis. This work identified metabolic conditions that make TPI dispensable for M. tuberculosis growth in culture and proved that M. tuberculosis relies on a single TPI enzyme and has no metabolic bypass for the TPI-dependent interconversion of dihydroxyacetone phosphate and glyceraldehyde-3-phosphate in glycolysis and gluconeogenesis. Finally, we demonstrate that TPI is essential for growth of the pathogen in mouse lungs.